Peran Ekstrakurikuler Sepak Bola dalam Mengembangkan Disiplin dan Pengendalian Diri pada Remaja Pengguna Gadget Intensif - Burhan, Zakir (Multidisciplinary Research Journal, 2025)
This study examines the role of school-based football extracurricular programs in improving discipline and self-control among adolescents who engage in intensive gadget use. Excessive gadget engagement has been shown to negatively impact adolescents’ behavioral regulation, attention span, and daily routines, and school sports are considered a promising intervention to counter these effects. Using a mixed-methods approach, the research involved 60 high school students who participated in a structured football program over twelve weeks. Quantitative data were collected through validated behavior discipline and self-control scales, while qualitative insights were gained from interviews with coaches and participants. The results revealed significant improvements in time discipline, compliance, emotional regulation, and impulse control after consistent involvement in the football program. Participants reported that the structured training, social accountability, and rule-based environment helped reduce gadget dependency during daily activities. The study concludes that football extracurriculars can serve as an effective behavioral intervention for adolescents with high gadget exposure. Implications for school policy and recommendations for future research are also discussed.